Timing of sequential use of double‐balloon catheter and oral misoprostol for induction of labor. Issue 11 (19th September 2016) - Kehl, Sven; Böhm, Lena; Weiss, Christel; Heimrich, Jutta; Dammer, Ulf; Baier, Friederike; Sütterlin, Marc; Beckmann, Matthias W.; Faschingbauer, Florian
Abstract: Aim: The best time to commence cervical ripening with a balloon catheter is unknown. The aim of this study was to evaluate whether application of a balloon catheter in the morning or in the evening is better when sequential prostaglandin application is planned. Methods: This multicenter historical cohort study included 415 women with an unfavorable cervix undergoing labor induction at term. Labor was induced with a double‐balloon catheter and the sequential use of oral misoprostol if necessary. The balloon catheter was placed in the morning group between 02:00–15:00 and in the evening group between 15:00–02:00. The primary outcome measure was the cesarean section rate. Secondary outcome measures included failed labor induction (no vaginal delivery within 72 h). Results: The cesarean section rate did not differ between the groups (morning 26.9%, evening 24.3%; P = 0.5553); however, more women in the morning group did not deliver within 72 h (8.8% vs 3.1%; P = 0.0138). In nulliparous women, labor induction failed more often in the morning group (12% vs. 4%, P = 0.043). In parous women, the induction‐to‐delivery interval was longer in the morning group (1756 vs. 1349 min; P = 0.046), and there were fewer deliveries within 24 h (35% vs. 56%, P = 0.016). Conclusions: When sequential use of a double‐balloon catheter and oral misoprostol for labor induction is planned, the preferable time for catheter placement is in the evening. This resulted in fewer failed inductions in nulliparous women and a shorter induction‐to‐delivery interval and more deliveries within 24 h in parous women.